Soziale Gerechtigkeit in Zeiten der Globalisierung und Individualisierung: Zum Wandel parteipolitischer Konzepte - Lohauß, Peter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2018)
The fundamental concepts of DGB, SPD and CDU and their current debate of new programs are examined for the change in the concepts of social justice. Both large parties now define social justice in terms of subordination under the economic constraint of the labour market. The long overdue solutions for the change of the system of social security regarding equality of generations and gender and thus the draft of a modern conception of social justice is still pending.